Co-gasification reactivity and synergy of banana residue hydrochar and anthracite coal blends. (15th September 2019) - Mosqueda, Alexander; Wei, Juntao; Medrano, Katleya; Gonzales, Hazel; Ding, Lu; Yu, Guangsuo; Yoshikawa, Kunio
Highlights: Effect of biomass hydrothermal treatment on co-gasification reactivity and synergy was studied. Co-gasification synergistic effect was weakened at higher hydrothermal treatment temperature. Chemical structure evolution of coal char in co-gasification well correlated with co-gasification synergy. Abstract: This work investigated the influence of biomass hydrothermal treatment (HT) on co-gasification reactivity and synergy of anthracite coal and banana residue hydrochar (HTC) prepared at varying HT temperatures (180 °C, 200 °C and 220 °C). In addition, the effect of HTC char on chemical structure evolution of coal char in co-gasification process was studied to correlate the co-gasification synergy. The results revealed that the co-gasification reactivity of the blended chars was enhanced with decreasing HT temperature. Moreover, the differences in synergistic effect on co-gasification reactivity was greatly influenced by HT temperature, and a more pronounced synergistic effect was achieved at the lowest HT temperature (180 °C). This phenomenon could be well explained by the chemical structure variations of coal char during co-gasification. Active AAEM contained in HTC char showed positive effect on the chemical structure evolution of coal char, specifically on the decrease in the order degree of carbon structure as well as increase in the amount of amorphous carbon structure of coal char; furthermore, this positive effect was weakened as HT temperature increased, being more evident for HT temperature of 180 °C than 200 °C and 220 °C. The findings in this work would be useful in revealing the co-gasification synergy mechanism of biomass hydrochar and coal blends, and may provide valuable information on the relevance of HT to industrial-scale gasification systems.